2019
DOI: 10.3390/app9153013
|View full text |Cite
|
Sign up to set email alerts
|

FEM-Based Compression Fracture Risk Assessment in Osteoporotic Lumbar Vertebra L1

Abstract: This paper presents a finite element method (FEM)-based fracture risk assessment in patient-specific osteoporotic lumbar vertebra L1. The influence of osteoporosis is defined by variation of parameters such as thickness of the cortical shell, the bone volume–total volume ratio (BV/TV), and the trabecular bone score (TBS). The mechanical behaviour of bone is defined using the Ramberg–Osgood material model. This study involves the static and nonlinear dynamic calculations of von Mises stresses and follows statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
2
8
0
2
Order By: Relevance
“…However, these studies mainly focused on the pedicle screw system's fixation strength rather than quantitatively analyzing the local biomechanical response proposed in the present study. In fact, the analysis of stress distribution and peak/average stress levels are thought to be relevant for fracture risk assessment (Maknickas et al, 2019;Takano et al, 2017;Keyak et al, 1997). Our results, also in agreement with data reported in Sawa et al (2016) for the cortical bone, seem to support the findings reported in Youssef et al (1999), Cho et al (2010), Hussain et al (2009), Mohi Eldin (2014, indicating a medial and caudal trajectory as the most advantageous.…”
Section: Discussionsupporting
confidence: 92%
“…However, these studies mainly focused on the pedicle screw system's fixation strength rather than quantitatively analyzing the local biomechanical response proposed in the present study. In fact, the analysis of stress distribution and peak/average stress levels are thought to be relevant for fracture risk assessment (Maknickas et al, 2019;Takano et al, 2017;Keyak et al, 1997). Our results, also in agreement with data reported in Sawa et al (2016) for the cortical bone, seem to support the findings reported in Youssef et al (1999), Cho et al (2010), Hussain et al (2009), Mohi Eldin (2014, indicating a medial and caudal trajectory as the most advantageous.…”
Section: Discussionsupporting
confidence: 92%
“…In the comparative studies of Kayak et al [ 55 ] and Tellache et al [ 56 ], dealing with the examination of stress- and strain-based failure theories applied to femoral bone fracture prediction, it was stated that the Huber–von Mises–Hencky criterion was robust. This criterion is frequently applied for the trabecular bone failure prediction, for example in [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mecmesin AFG25 cell-controlled deformation was measured with an accuracy of ±0.01 mm, and the compressive force ranged from 2 to 2,500 N, with an accuracy 100 of ±0.1% and a cross-speed accuracy of ±0.1%. The experiment examined the mechanical qualities of the imprinted 3D model of the lumbar spine using this device ( Maknickas et al , 2019 ). Each vertebra was compressed with 950 N. The selected speed was 1 mm/minute ( Fig.…”
Section: Case Detailsmentioning
confidence: 99%